Patriarchy, political enmity, and domestic violence: Exploring abusive mixed intimate partnerships in a conflict zone - Erez, Edna (International review of victimology, 2022)
Mixed couples face more marital conflict than endogamous couples. Drawing on intersectional theory and narrative victimology, this study examines women’s accounts of abuse in mixed heterosexual Arab/Palestinian–Israeli Jewish intimate partnerships amid the Israeli–Palestinian conflict. The narratives of 25 women formerly in an abusive relationship are the primary data, which are supplemented by a comprehensive list of calls seeking advice or intervention from a non-governmental organization (NGO) that assists women in mixed relationships, and the NGO’s recorded in-service training sessions during which social workers discuss clients’ plights and abuse exposure. Consistent with research on mixed couples, the women’s narratives connect their abuse to differences, dynamics, and tensions rooted in cultural, religious, and social beliefs and practices. Importantly, the narratives also highlight how the Israeli–Palestinian conflict amplifies and escalates the women’s abuse. Intersections of gender, religion, and nationality as well as life in a conflict zone critically affect the abuse dynamic the women experience. The article concludes with a discussion of the relevance of narrative victimology and political enmity for intersectional approaches to domestic violence.